Searching for the Family Doctor : Primary Care on the Brink - Hoff, Timothy, 1965- (Book collections on Project MUSE., 2022)
Exploring how to save primary care by giving family doctors a fighting chance to become the generalists we need in our lives, Searching for the Family Doctor is required reading for anyone interested in the troubled state of modern medicine.